Incidence of Adverse Reactions to Parenteral Thiamine in the Treatment of Wernicke's Encephalopathy, and Recommendations. (30th September 2019) - Thomson, Allan; Guerrini, Irene; Marshall, Elizabeth Jane
Abstract: Aim: To offer an estimate of the incidence of anaphylactic reactions to parenteral products containing thiamine used in the treatment of Wernicke's encephalopathy (WE) and make recommendations. Method: Review of previously released data on some older products and parenteral thiamine use in some other countries; analysis of sales and adverse incident data on anaphylaxis for a contemporary parenteral product used in the UK, Pabrinex. Results: It was difficult to estimate the incidence of related anaphylactic reactions to Pabrinex in the UK because the number of doses given is unknown. Sales data are only an approximation to doses given because for products with a limited shelf life not all product sold is administered. However, available data indicate that there have been 10 anaphylactic reactions to Pabrinex from between 5, 431, 235–6, 651, 947 patient-days (14, 880–16, 080 years) of treatment. Conclusion: It is reasonable to assume that the risk of anaphylaxis is low, and lower than for many other drugs. The risk-benefit ratio for administration is favourable given the potential severity of brain damage in Wernicke–Korsakoff (WK) syndrome. There is a need for international agreement on the reporting of anaphylaxis and on the optimum thiamine therapy for the treatment of WK syndrome. We make recommendations on how this might be achieved.